The inhibitory effect of celecoxib and rosiglitazone on experimental endometriosis - Olivares, Carla Noemi (2011)
To evaluate the effects of celecoxib and rosiglitazone on the implantation and growth of endometriotic-like lesions in a murine model of endometriosis.